Pulmonary Nodule Size <5 mm Still Warrants Investigation in Patients With Osteosarcoma and Ewing Sarcoma. Issue 3 (April 2017) - Kusma, Jared; Young, Cody; Yin, Han; Stanek, Joseph R.; Yeager, Nicholas; Aldrink, Jennifer H.
Abstract : Background: Osteosarcoma (OS) and Ewing sarcoma (ES) have a high propensity to develop pulmonary metastases. Lung lesions with calcification, peripheral location, and size >5 mm are more likely to represent malignant metastases. We evaluated the incidence of malignancy in nodules 5 mm or less to potentially guide decisions between biopsy and observation. Materials and Methods: A retrospective review of patients <25 years of age with metastatic OS and ES treated at our institution between 2001 and 2014 who had undergone pulmonary nodule biopsy was performed. Computed tomographic scans were reviewed to evaluate nodule size and change over time. Results: Thirty-five patients (27 OS, 8 ES) met inclusion criteria. One hundred sixteen nodules were biopsied (97 OS, 19 ES). Nodule size at biopsy was not significantly different between the malignant (median, 6 mm, range, 1 to 79 mm) and benign (median, 3 mm, range, 1 to 21 mm) lesions ( P =0.063). Size of pulmonary nodules <5 mm was not entirely predictive of benign status, with sensitivity estimate of 0.709 (95% confidence interval, 0.465-0.872; P =0.091) and specificity estimate of 0.776 (95% confidence interval, 0.324-0.962; P =0.219) for all nodules biopsied. Conclusions: Pulmonary nodules in patients with OS and ES <5 mm cannot be excluded from biopsy considerations.